An Empirical Analysis of the Determinants of Corporate Social Responsibility Disclosure in Indonesia - Iyaz Rahma Salsani; Nursiam Nursiam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research was conducted to measure the impact of green accounting, public share ownership, profitability, and media exposure on corporate social responsibility disclosure. The sample selection method is associative quantitative with sample acquisition using a purposive sampling model and then there is 116 company data, all of which are companies indexed in LQ45 and publish annual reports on the BEI in the 2019-2022 period. This secondary data source was then processed using SPSS by testing classical assumption analysis and multiple regression. Through empirical evidence, it is revealed that corporate social responsibility disclosure can be influenced by green accounting, while disclosure of social responsibility values cannot be caused by the influence of public share ownership, profitability, and media exposure.